Sri Lanka: School leadership in the conflict-affected north and east - Earnest, Jaya (Routledge, 2013)
The 30-year ethnic civil war between the Government of Sri Lanka (GoSL) and the Liberation Tigers of Tamil Eelam (LTTE) ended in mid 2009. This conflict seriously undermined the country’s enormous development potential. Approximately 800,000 people, a third of whom were children, were displaced. Nearly a million children, amongst them an estimated two thousand child soldiers, lived in the north and the east of the country, the areas most affected by the ethnic conflict. The impact of the tsunami of December 2004 exacerbated the situation here. Furthermore, the peace efforts of international mediators, notably Norway, were thwarted by uprisings in 2006 and 2008. However, the Sri Lankan military finally defeated the Tamil Tigers, marking the end of the civil war. This chapter examines school leadership in the districts of north and east Sri Lanka, drawing on fieldwork undertaken in 2006 (Earnest and Finger, 2006) and subsequent field narratives obtained in 2010 and 2011. It comprises three main sections. First, the background of the civil war and the impact of the tsunami in 2004 are considered. Second, an overview is presented of the structure and administration of the current Sri Lankan education system. Third, the realities of school leaders’ work are examined in order to identify some of the challenges they face.